The Effect of Safety Leadership on Safety Compliance: The Mediation Role of Safety Behaviors and Safety Motivation - Tahapary, Kevin Yosua; Laksono, Ali Ridho (Manunggal Halim Jaya, 2025)
This study identifies problems that arise due to neglect or reduction in the use of necessary personal protective equipment (PPE), as well as the lack of routine inspection of the condition of PPE at PT. PRIA. In this context, the study examines the effect of safety leadership on safety compliance by considering the mediating role of safety behaviors and safety motivation. The method used in this study is a quantitative approach with a causal design. Data were collected through an online questionnaire distributed to 250 respondents using a purposive sampling. The independent variable in this study is safety leadership, while the dependent variable is safety compliance. Safety behaviors and safety motivation function as mediating variables that are expected to explain the relationship between safety leadership and safety compliance. Using a quantitative explanatory methodology, the research utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS), which was used in this work via SmartPLS software. A structured survey was used to gather information from 250 employees in PT. PRIA. The findings reveal a positive relationship between safety leadership and safety compliance, considering the mediating role of safety behaviors and safety motivation.